The degree of practicing the leadership skills by school principle at Qasbat Almafraq directorate of education from the teachers' perspective - Harahshah, Emad Khalaf (Journal of Educational and Psychological Sciences, 2020)
The study aimed at identifying the degree that the school principals for the leadership skills at Qasbat Almafraq directorate of education from the teachers’ perspective in the light of gender, scientific qualification, and years of experience variables. The researcher used the descriptive approach, and developed a questionnaire consisting of (35 items). The questionnaire was divided into five sections. The randomly chosen sample of this study consisted of (615) male and female teachers from Qasbat Almafraq directorate of education. The results of the study showed that the degree of practicing leadership skills by the school principals at Qasbat Almafraq directorate of education from the teachers’ perspective was intermediate and the study found that there are not statistically significant differences for the study sample estimates on the degree of practicing leadership skills by the school principalsat Qasbat Almafraq directorate of education due to the variable of sex came. The study also found that there are statistically significant differences attributed to the variable of scientific qualification in favor of those who have postgraduate studies. It found that there are statistically significant differences due to the variable of years of experience and the differences came in favor of those with long experience.Based on the results of the study, the researcher recommends developing leadership skills among school principals through their participation in training courses to enhance these skills.
Keywords: leadership skills; schools principles; Qasbat Almafraq directorate of education; Jordan